2015
DOI: 10.17116/jnevro20151156124-32
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the efficacy and safety of antidepressant therapy in patients of a geriatric psychiatric unit

Abstract: Antidepressant/carnicetine combination therapy may be recommended for treatment of depression in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many clinical studies ( 44 , 45 ) have confirmed that, compared with established antidepressants, ALC can significantly reduce depressive symptoms and have similar effects. However, no studies have reported the changes of LC and ALC levels in patients after antidepressant treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Many clinical studies ( 44 , 45 ) have confirmed that, compared with established antidepressants, ALC can significantly reduce depressive symptoms and have similar effects. However, no studies have reported the changes of LC and ALC levels in patients after antidepressant treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Many clinical studies [38][39] have con rmed that ALC can signi cantly reduce the symptoms of depression compared with the established antidepressants and has similar effectiveness. However, no studies have reported the changes of LC and ALC levels in patients after treatment with antidepressant drugs.…”
Section: Discussionmentioning
confidence: 99%